Corak Tafsir Maqashidi Dalam Tafsir Nazm Al-Durar Fi Tanasub Al-Ayat Wa Al-Suwar Karya Al-Biqa‘I - Wardatutsaniyah, Tiara; Al Mufaddilah, Ni’mah (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2024)
Al-Biqa'i was a mufasir who lived around 809 Hijriyah. His work in the intellectual world has produced a book which has become a magnum opus, namely the book Nazm al-Durar fi Tanāsub al-Āyāt wa al-Suwar. In terms of methodology, Tafsir Al-Biqā'ī uses the method of interpreting the AlQur'an verse by verse and letter by letter sequentially according to the arrangement of the verses and letters in the Al-Qur'an (tahlili), with the style used being language (lughawi). This research uses qualitative methods with a library research approach. This article finds that there are interpretation styles other than linguistic styles, namely the maqashid style used by al-Biqa'i in interpreting the Al-Qur'an. Al-Biqa'i uses maqashid surah in his maqashid approach. Al-Biqa'i revealed that the surahs of the Qur'an have a main theme and other themes within them. The name of the surah is taken from the main theme of the surah. So according to al-Biqa'i, in finding the maqashid of a surah, you must know the theme contained in the surah and to find it, you need to review the contents of the surah by looking at the relationships in the Al-Qur'an.